Belonging: a review of conceptual issues, an integrative framework, and directions for future research - Allen, Kelly-Ann; Kern, Margaret L.; Rozek, Christopher S.; McInerney, Dennis M.; Slavich, George M. (Australian journal of psychology, 2021)
Objective: A sense of belonging - the subjective feeling of deep connection with social groups, physical places, and individual and collective experiences - is a fundamental human need that predicts numerous mental, physical, social, economic, and behavioural outcomes. However, varying perspectives on how belonging should be conceptualised, assessed, and cultivated has hampered much-needed progress on this timely and important topic. To address these critical issues, we conducted a narrative review that summarizes existing perspectives on belonging, describes a new integrative framework for understanding and studying belonging, and identifies several key avenues for future research and practice. Method: We searched relevant databases, including Google Scholar, PubMed, Scopus, PsycInfo, and ClinicalTrials.gov, for articles describing belonging, instruments for assessing belonging, and interventions for increasing belonging. Results: By identifying the core components of belonging, we introduce a new integrative framework for understanding, assessing, and cultivating belonging that focuses on four interrelated components: competencies, opportunities, motivations, and perceptions. Conclusion: This integrative framework enhances our understanding of the basic nature and features of belonging, provides a foundation for future interdisciplinary research on belonging and belongingness, and highlights how a robust sense of belonging may be cultivated to improve human health and resilience for individuals and communities worldwide. KEY POINTS What is already known about this topic: Belonging is a fundamental human need that all people are driven to satisfy. However, there is disagreement in the literature regarding how a person should go about increasing their sense of belonging. There is also little consensus regarding how belonging should be conceptualized and measured. What this topic adds: The review article draws together disparate perspectives on belonging and harnesses the strengths of this multitude of perspectives to help advance the field. The paper provides a framework that can help inform researchers, practitioners, and individuals seeking to increase a sense of belonging in themselves and in the organizations and groups in which they work and live. We posit that competencies, opportunities, motivations, and perceptions are central elements in strategies that can be used to increase our individual and collective sense of belonging for the betterment of society.